The Mechanics Accuracy of Students’ Writing - Lilik Yuliawati (Universitas PGRI Madiun, 2021)
In writing courses, the students tend to be more aware of technical errors in writing including the mechanics. Conversely, they tend to focus more on the idea or content of their writing when they produce papers to fulfill the assignment of non-writing courses. Whereas, the punctuation errors and misspelled words will make the meaning of the sentence ambiguous. This study aims to find out the degree of mechanics accuracy of students’ writings and what kind of mechanics mistakes mostly produced. The mechanics that were analyzed include punctuation, capitalization, spelling, italicization, and numbering of 65 writing assignments of three non-writing courses. The method used in this study was content analysis. The result of this study revealed that there were number of mechanics mistakes in students writing assignments, but those mistakes did not greatly affect readers’ understanding. The punctuation using of students’ writing assignments was 41% accurate; the capitalization using was 82% accurate; the spelling using was 83% accurate; the italicization using was 96% accurate; and the numbering using was 98% accurate.